Private securities litigations against foreign firms: empirical findings - Alanko, Reeta (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: As foreign firms all over the world are increasingly cross-listing on U.S. stock exchanges, there is a vigorous discussion going on among academics as to why foreign firms cross-list on a U.S. stock exchange. One of the most discussed reasons is the 'bonding hypothesis' according to which foreign firms cross-list on US stock exchanges in order to leapfrog their home countries' weak legal institutions by agreeing to abide by U.S. securities regulations. The bonding hypothesis is criticized by several academics for two reasons. First, foreign firms are bound to a different, and arguably to a less stringent securities regulation regime. Second, the Securities Exchange Commission is criticized for insufficient enforcement of its rules on foreign issuers. However, most of these studies have disregarded private securities litigation as a way to enforce bonding with the U.S. regulatory regime. This paper is an exploratory study that presents an overview of the academic discussion relating to the bonding hypothesis and to constructively reflect on the critique against it. I find that large accounting scandals during recent years have induced the Congress to enact more severe corporate governance regulations for both foreign and domestic firms. Foreign firms are increasingly treated equally with domestic firms. Nevertheless, the standards remain lower for foreign firms today. Even though the extraterritorial reach of U.S. securities filing requirements is limited, the U.S. courts have been able to establish a broader extraterritoriality for the U.S. securities fraud provision. Thus foreign firms with a lower level of commitment to the U.S. markets (level I ADR) are held liable under the U.S. securities fraud provisions. Consequently, the threat of securities litigation under securities fraud provisions bond the foreign firms to the U.S. corporate governance regime and to the same insider trading rules than the U.S. based firms are bound to. Thus, private securities litigation has an opportunity to serve as a mechanism to enforce bonding with the U.S. securities regulation. The descriptive analysis confirms the findings of literature review and reveals that foreign firms are increasingly interested in cross-listing on the NYSE and voluntarily bonding to the most stringent securities regulations. Most of the new cross-listing on the NYSE are from civil law countries and from emerging markets. This finding is consistent with the prior research on the bonding hypothesis that firms from lower corporate governance regime are motivated the most by the bonding reasons to cross-list. The data reveal that the private securities cases enforce foreign firms to bond to the U.S. securities regime. Foreign firms are treated uniformly with domestic firms, and the likeliness to get sued is equivalent for both foreign and domestic firms.